Mitigation of heterocyclic aromatic amines in cooked meat. Part I: Informed selection of antioxidants based on molecular modeling. (30th November 2020) - Meurillon, Maïa; Angénieux, Magaly; Mercier, Frédéric; Blinet, Patrick; Chaloin, Laurent; Chevolleau, Sylvie; Debrauwer, Laurent; Engel, Erwan
Highlights: Analog design strategy to make a reasoned choice of antioxidants for HAA inhibition. Determination of the structural properties required for inhibiting HAA formation. Tests of HAA inhibition by 4 active principles and 4 natural ingredients. Best formulations to reduce HAA formation. Abstract: This work aimed to develop a method permitting an informed choice of antioxidants to reduce carcinogenic heterocyclic aromatic amine (HAA) formation during proteinaceous food cooking. Therefore, a three-step approach was developed. First, the most promising antioxidants were selected using molecular modeling approaches. For this, analog design was used to highlight the most suitable antioxidants based on their diversification potential using bioisosteric replacement. Then, structure activity relationship studies allowed drawing the relevant properties for inhibiting HAA formation and explained partly the inhibitory activity. Secondly, the approved antioxidants were tested in ground beef patties to assess their inhibitory properties against HAA formation. Resveratrol was found to be the most efficient as it totally inhibited MeIQ and reduced MeIQx and PhIP formation by 40 and 70%, respectively. Finally, natural ingredients rich in these antioxidants were evaluated. Oregano was found to totally inhibit MeIQ formation and to reduce by half MeIQx and PhIP formation.